The Lecturer’s Perspective on Task-Based Language Teaching in an Indonesian Higher Education Setting - Yunus, Muhammad; Halijah, Sitti; Kordja, Baharuddin; Henny, Agussari; Jamal, Mardhiana (ELT Worldwide: Journal of English Language Teaching, 2024)
This study explores lecturers' perspectives on Task-Based Language Teaching (TBLT) in an Islamic university in South Sulawesi, focusing on its effectiveness in enhancing student competencies, skill development, and knowledge retention. Using a survey method, data were collected from 20 lecturers representing various disciplines, including English Literature, Indonesian Literature, Arabic Literature, Communication Studies, and Language Education programs. The results show a strong consensus (90%) in favor of TBLT, particularly regarding its role in fostering linguistic competence, cognitive skills, and student engagement. Lecturers overwhelmingly agree that task repetition and assignments before, during, and after class are effective in promoting long-term memory retention and real-world application of language skills. However, some nuanced perspectives on task timing and classification indicate areas for further research and refinement in TBLT implementation. Overall, this study contributes to the growing body of literature on task-based approaches in higher education, offering practical insights into its pedagogical benefits and challenges.